THE AFRICAN EXPERIENCE AND WORLD SYSTEM ANALYSIS: A COMPREHENSIVE REVIEW OF INTERNATIONAL RELATIONS THEORY - M, Rapanyane; K, Shai (Economics and Statistics Research Journal (ESRJ), 2022)
This research paper provides a comprehensive and critical analysis of World System Analysis (WSA), also known as World System Theory, as a critical theory in International Relations. The paper examines the strengths and weaknesses of WSA and compares it with Dependency Theory. The paper focuses on the Afrocentric paradigm to analyze WSA, arguing that it is the best tool to understand world politics, world history, imperialism, global inequality, dependency, and power. The authors argue that WSA is broader in perspective than Dependency Theory, as it places the world at the center of attention in analyzing world economic distribution instead of the nation-state. The paper also traces the historical development of WSA, its relationship with capitalism, and the divisions in the world that it identifies. Methodologically, the paper uses a qualitative approach, relying on secondary sources such as relevant journal papers, periodicals, books, and websites. The authors provide fitting definitions of the theory, its key assumptions and arguments, and the main features of the theory. The paper critically examines the implications of WSA in IR and compares it with other critical theories. The authors take positions on the key arguments of WSA and provide a fair and justifiable explanation of the theory. In conclusion, this paper contributes to the literature on critical IR theories by providing a thorough analysis of WSA’s central arguments, assumptions, and implications. The Afrocentric paradigm used in the analysis offers a unique and insightful perspective, allowing for a fuller understanding of WSA and its implications. The paper underscores the need for a critical understanding of global inequality, dependency, and power and highlights WSA’s potential to offer such an understanding